Retrieval-Induced Forgetting in the Feigning Amnesia for a Crime Paradigm - Mangiulli, Ivan; van Oorsouw, Kim; Curci, Antonietta; Jelicic, Marko (Frontiers in Psychology, 2019)
Previous studies demonstrated that, when asked to honestly provide information about a mock crime, former feigners performed worse than those who were requested to confess to this event. Thus, feigning amnesia for a mock crime undermined genuine memory for the same experience. In the present study, we examined whether retrieval-induced forgetting (RIF) underlies this memory-undermining effect. After watching a mock crime, participants had to feign amnesia or confess to having committed that crime. Feigners were given retrieval practice instructions (i.e., retrieval-practice group) or no further instructions (i.e., control group). Immediately and one day later, all participants had to genuinely report what they remembered about the crime. Although simulators in the retrieval-practice group recalled the largest amount of information as a positive consequence of retrieval, the ratio for crucial crime-related details was lower than that exhibited by both simulators that were given no instructions and confessors. These findings suggest that RIF might play a role in forgetting critical information in claims of crime-related amnesia. Theoretical and practical implications will be discussed.